Audrey Truschke (2017). Aurangzeb. The life and legacy of India’s most controversial king. Stanford, CA.: Stanford University Press, 152 pp. - Ramírez Reyes, María Fernanda; Alvarado Becerril, Maribel Elliet (Estudios de Asia y África, 2018)
Audrey Truschke (2017). Aurangzeb. The life and legacy of India’s most controversial king. Stanford, CA.: Stanford University Press, 152 pp.